Lived Institutions as History of Experience - Annola, Johanna; Lindberg, Hanna; Markkola, Pirjo (Palgrave Studies in the History of Experience, 2024)
This open access book focuses on institutions that were produced and formed by the emerging welfare state. How were institutions experienced by the people who interacted with them? How did institutions as sites of experience shape and structure people's everyday lives? Histories of institutions have mainly focused on the structures and power relations produced by institutional settings. Likewise, despite an extensive historiography of the welfare state, reflections on individuals' experiences of welfare are few. By using 'lived institutions' as its conceptual frame, this edited collection merges the fields of institutional studies, the history of the welfare state - and the novel and vibrant field of the history of experience.